METODOLOGI STUDI HADIS DALAM ERA DIGITAL: TANTANGAN DAN SOLUSI - hira, naal; Nurul Islamiyah; Mohammad Salik (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Hadith studies, as a fundamental discipline in understanding Islamic teachings, are facing significant transformations in the digital era. This era offers easy access to unlimited data and a paradigm shift in automated hadith searches, supported by various software and digital databases. However, this progress also poses crucial challenges, such as the spread of fake hadiths, data vulnerability, and the need for researchers' digital literacy, which demands adaptation of hadith study methodologies. This study aims to examine these adaptations, analyze the challenges, and offer innovative solutions to ensure the validity and authenticity of hadith studies amidst the flow of digital information. Using a descriptive qualitative method, this study obtained primary data through expert interviews and observations of digital platforms (Maktabah Syamilah, Al-Maktaba Al-Waqfiyyah), as well as secondary data from the literature. Thematic analysis was conducted through transcription, coding, and interpretation of meaning. The results show that the digital era has increased accessibility and changed the paradigm of hadith searches. However, challenges arise in the validation of digital sources, technological dependence that shallows analysis, ethical/copyright issues, and variations in digital literacy. The discussion emphasizes that solutions involve the development of integrated applications, increasing digital literacy, collaboration between institutions, and strengthening traditional hadith criticism methodologies. Technology should function as a support to strengthen the foundation of hadith science, making hadith studies more efficient and accurate. Keywords: Digital Era; Hadith; Methodology; Solution; Challenge.